Subjective Well-Being in People with Nephrotic Syndrome: Exploring Role of Lifestyle and Self-Confidence - Rahel Julia Natali; Arthur Huwae (Bulletin of Counseling and Psychotherapy, 2023)
Sufferers of nephrotic syndrome can be found in both developed and developing countries. All individuals afflicted with nephrotic syndrome, including both children and adults, often experience a loss of hope and find it challenging to attain subjective well-being in their lives. Therefore, this research aims to determine the portrait of subjective well-being in people with nephrotic syndrome by examining the components and factors that influence subjective well-being. The method employed in this research is descriptive qualitative phenomenology. The data collection process in this study utilizes data triangulation, including observation, interviews, and document analysis. Data analysis was conducted using interactive data analysis methods. The findings of this study indicate that, in general, individuals suffering from nephrotic syndrome tend to have low subjective well-being or face difficulties in achieving it in their lives. This is primarily due to individuals being unable to fulfill the components and factors of subjective well-being, often experiencing higher negative affect than positive affect. Additionally, researchers have identified new factors that influence subjective well-being, namely lifestyle and self-confidence.